PENGARUH PENGGUNAAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKn - Kalsum, Umi; Sulistyarini, Sulistyarini; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of using scramble learning model for students' learning outcomes in Civic Education subject at class XII of SMA Negeri 5 Pontianak. The method of research is the experimental method using Quasi Experimental Design, Nonequivalent Control Group Design. The subject of this research was the class XII Science 2 (as experimental class) and XII Science 3 (as control class). This research instrument consist of multiple choice with 20 questions. The student learning outcomes of experiment class before and after treatment with scramble learning model, the averages pre-tests and post-test is 66.25 and 84.58. While the results of the student learning control class before and after given treatment conventional learning, the averages pre-test and post-test is 64.30 and 78.33. Based on the paired sample ttest on the value 0.000<0.005 therefore, Ho was rejected and Ha is accepted. Based on the calculation of the effect size experiment class is 3.317>1.00 and for control class is 1.98>1.00. In conclusion, theres is an effect in the use of scramble learning model towards students learning outcomes in Civic Education in class XII Science 2, compared with an effect of conventional learning models in class XII Science 3.Â Keywords: Learning Model Scramble, Learning Outcomes, Civic Education